Financing of Czech transport as a key problem of further appropriate level of transport services - Peltrám, Antonín; Kořínková, Květoslava (Univerzita Pardubice, 1996)
The density of the Czech transport infrastructure is rather high, but mainly because of bad maintenance with low quality. There are some methodological problems, partially as a heritage of the previous techniques, that is necessary to change (forecasting of future demands, necessary capacities etc.). Some of them are described with more details.
Financování české dopravy ze základního problému pro budoucí oblast dopravní obslužnosti
Die Finanzierung des Tschechischen Verkehrs aus einem Grundproblem für zukunftiges Niveau der Verkehrsleistungen